Floating architecture construction on and near water - Stopp, Horst; Strangfeld, Peter (Schwimmende Architektur - Bauen am und auf dem Wasser ;, 2017)
Floating architecture is not only an issue for luxurious tourism, but with the climatic change the building of floating structures becomes relevant for many areas in the world. In regions with rising sea levels, frequent flooding, or thawing permafrost, floating structures can be a solution to adapt existing settlement areas to these new conditions. The self-sufficient energy and supply systems required for floating settlements can also be used in rural areas with a lot of migration. This collection presents papers of conferences organized by the Faculty of Architecture and Urban Planning at Brandenburg University of Technology Cottbus-Senftenberg (BTU).